A study of Coxsackie B virus infections, 1972-1983. - Bell, E. J. (Cambridge University Press, 1984)
The results of a twelve-year study of Coxsackie B virus (CBV) infections in patients with a variety of acute and chronic illnesses are reported. CBVs were isolated from only 123 patients most of whom were children with respiratory illness. Virus diagnosis in adults was based mainly on the detection of significant rising or static high neutralizing antibody titres. Between 1972 and 1979 most investigations centred on patients with suspected viral heart disease, 12% of whom were found to have diagnostically significant CBV titres. In studies on patients with definite myo-pericarditis the number positive increased to 33%. In 1980 clinical interest switched to the possible role of CBV in myalgic encephalomyelitis (ME), an illness of diverse symptomatology. Investigation of suspected cases of ME in 1983 showed that 16% were serologically positive compared to 4% of normal adults in the West of Scotland. In patients with well-documented ME this figure rose to 41%. The demand by clinicians for CBV neutralizing antibody tests has increased over the past twelve years and continues to escalate annually, especially in patients with chronic relapsing illness.